Critical Reflection and Imaginative Engagement: Towards an Integrated Theory of Transformative Learning - John M. Dirkx; Benjamin D. Espinoza; Steven Schlegel (Adult Education Research Conference, 2018)
Based on a review of the literature, we propose an integrated approach to transformative learning that recognizes the importance of both the rational and affective, as well as the personal and the social dimensions in fostering self-understanding.
Keywords: transformative learning; affective experiences; self-understanding